Dissimilar Perspectives and Facts about Procedure of Amenorrhea between Fledgling Ladies - Rohana Salam, Sajawal Mir, Jamshaid Alam, Hina Manzoor, Rubina Kousar, Talha Shabbir, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This investigation work aimed to find out the awareness and numerous perspectives towards the procedure of mensuration between ladies of fledgling age. Methodology: This descriptive investigation work carried out in Jinnah Hospital, Lahore and its remote areas from December 2017 to November 2018. The selection of the 500 ladies carried out from remote areas of hospital and students of this institute with the help of non-probability sampling method. Ladies present with the abnormalities in amenorrhea procedure or suffering from other gynecological problems were excluded from this investigation work. All the selected ladies were in their menstruating age regardless of their marriage and education stage. SPSS V. 22 was in use for the arithmetical exploration of the collected information. We recorded all the information of a well-organized Performa. Results: Out of total five hundred participants, 84.5% (n: 415) ladies stated that this procedure is beneficial for health; however, 18.5% (n: 85) felt that this incident was not healthy. Out of total five hundred ladies, 88.65% (n: 438) ladies regarded the procedure of amenorrhea as normal procedure, while 13.45% (n: 62) ladies thought this as God’s curse. Conclusion: Health education of the ladies particularly living in the rural areas is much necessary. Health education will prepare the ladies emotionally to face this procedure of amenorrhea with less adverse reactions. Faulty perception, un-acfactsment and unsecure practices about the procedure of amenorrhea are very common between ladies of fledgling age. Keywords: Arithmetical, exploration, unsecure, Sampling, amenorrhea, Performa, abnormalities.